The Life of Elisabeth Vigée Le Brun as an Example of an Artist’s Biography at the Turn of the 18th-19th Centuries - Abramkin, Ivan A. (Actual Problems of Theory and History of Art, 2018)
The analysis of Elisabeth Vigée Le Brun’s biography in the context of European and Russian culture at the turn of the 18th-19th centuries is presented in the article. As it supposed to be, the thesis should be reviewed. So, the main aim of the article is to compare Elisabeth Vigee Le Brun’s biography and life of romantic artists in Russia (Orest Kiprenskii, Vladimir Orlovskii, Vasilii Tropinin, Aleksandr Varnek and Silvestr Shchedrin). Despite the fact that numerous studies discuss different romantic artists’ biographies, none of them is devoted to comparison between life of sentimental and romantic artists. Besides, there are a few studies on Elisabeth Vigée Le Brun’s art in Russian. So, Elisabeth Vigée Le Brun’s life seems similar to the romantic artists’ ones. Therefore, it is important to compare the biographies of different artists in order to supplement and rethink stylistic definitions at the turn of the 18th-19th centuries (romanticism, sentimentalism).